Financial intermediary development and growth volatility : do intermediaries dampen or magnify shocks? - Beck, Thorsten, 1967- 1967- (Policy research working paper, 2001)
Panel data for 63 countries in 1960-97 reveal no robust relationship between the development of financial intermediaries and the volatility of growth